Anionic polymers amplify electrokinetic perfusion through extracellular matrices - Walker, Joseph C.; Jorgensen, Ashley M.; Sarkar, Anyesha; Gent, Stephen P.; Messerli, Mark A. (Frontiers in Bioengineering and Biotechnology, 2022)
Electrical stimulation (ES) promotes healing of chronic epidermal wounds and delays degeneration of articular cartilage. Despite electrotherapeutic treatment of these non-excitable tissues, the mechanisms by which ES promotes repair are unknown. We hypothesize that a beneficial role of ES is dependent on electrokinetic perfusion in the extracellular space and that it mimics the effects of interstitial flow. In vivo, the extracellular space contains mixtures of extracellular proteins and negatively charged glycosaminoglycans and proteoglycans surrounding cells. While these anionic macromolecules promote water retention and increase mechanical support under compression, in the presence of ES they should also enhance electro-osmotic flow (EOF) to a greater extent than proteins alone. To test this hypothesis, we compare EOF rates between artificial matrices of gelatin (denatured collagen) with matrices of gelatin mixed with anionic polymers to mimic endogenous charged macromolecules. We report that addition of anionic polymers amplifies EOF and that a matrix comprised of 0.5% polyacrylate and 1.5% gelatin generates EOF with similar rates to those reported in cartilage. The enhanced EOF reduces mortality of cells at lower applied voltage compared to gelatin matrices alone. We also use modeling to describe the range of thermal changes that occur during these electrokinetic experiments and during electrokinetic perfusion of soft tissues. We conclude that the negative charge density of native extracellular matrices promotes electrokinetic perfusion during electrical therapies in soft tissues and may promote survival of artificial tissues and organs prior to vascularization and during transplantation.